On the Semantic Dimensions of Personal Names in the Context of People and Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the formation of personal names in relation to the life, customs, and linguistic richness of different cultures, as well as their semantic dimensions. Personal names in various cultures are shaped by historical, religious, cultural, and social factors. Through examples from Uzbek, Russian, Arabic, and Western cultures, the article illustrates the semantic features, symbolic meanings, and national characteristics of names.